INVESTIGATING THE EFFICACY OF CURCUMIN NANOEMULGEL IN COMBATING BACTERIAL ACTIVITY USING AGAR DIFFUSION METHOD AND BROTH DILUTION METHOD - BOORAVILLI, JOSHNA; SIRISOLLA, JANAKI DEVI (International Journal of Applied Pharmaceutics, 2025)
Objective: The objective of this study was to develop a topical delivery formulation of curcumin nanoemulgel, evaluating its antibacterial activity against both Gram-positive and Gram-negative bacteria. Methods: Curcumin-containing nanoemulsion was developed by spontaneous emulsification technique. Using a central composite design, the formulation was selected and further evaluated for size analysis, zeta potential, and Scanning Electron Microscopy (SEM). Furthermore, the optimized curcumin nanoemulgel was evaluated for its antibacterial activity. Results: The in vitro antibacterial assay of curcumin nanoemulgel (CUR-CLO NEG 1) exhibits better antibacterial activity against Gram-positive Staphylococcus aureus (S. aureus.) than Gram-negative bacteria Escherichia coli (E. coli.). Inhibition zones of 27.34±0.15 mm (S. aureus.) and 25.32±0.54 mm (E. coli.) were observed by optimized nanoemulgel. Minimum Inhibitory Concentration (MIC) values against S. aureus. and E. coli. was 120 and 125 µg/ml, respectively. The agar diffusion method revealed significant inhibition zones for g-positive bacteria (S. aureus), whereas the broth dilution method confirmed its effective growth inhibition at lower concentrations in S. aureus. The results in this research work highlight the remarkable breakthrough of curcumin nanoemulgel as a highly effective antibacterial drug delivery system. Conclusion: The curcumin nanoemulgel retained its better antibacterial properties over drug free loaded nanoemulgel and curcumin plain gel. From the research work, it can be concluded that both the agar diffusion method and broth dilution method confirm the curcumin nanoemulgel's antibacterial activity against g-positive bacteria (S. aureus).